2022
DOI: 10.3390/ijms23052839
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transcriptional Regulation of Molecular Determinants during Cardiogenesis

Abstract: Cardiovascular development is initiated soon after gastrulation as bilateral precardiac mesoderm is progressively symmetrically determined at both sides of the developing embryo. The precardiac mesoderm subsequently fused at the embryonic midline constituting an embryonic linear heart tube. As development progress, the embryonic heart displays the first sign of left-right asymmetric morphology by the invariably rightward looping of the initial heart tube and prospective embryonic ventricular and atrial chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 376 publications
(466 reference statements)
0
13
0
Order By: Relevance
“… [ 14 ] Cardiac Tumors Clinical Details Addresses the topic of cardiac tumors, which is relevant for understanding the etiology and characteristics of cardiac myxoma (CM) [ 15 ] Cardiac Tumors Clinical Details Explores cardiac tumorigenesis [ 20 ] Heart Regeneration Human Samples Provides insights into heart regeneration, a relevant concept for studying the limited regenerative potential of cardiomyocytes. [ 21 ] Cardiac Regeneration Human Samples Explores cardiac regenerative potential [ 22 ] Cardiac Regenerative Pathways Human Samples Essential to investigate the nature of cardiomyocytes [ 23 ] Cardiac Organoids Human Samples Provides step by step progression of the cardiac development [ 24 ] Cardiac Organoids Human Samples Provides insights into the cardiac developmental processes [ 152 ] Cardiac Reprogramming Factors Histopathology Addresses the genetic architecture involved in cardiac reprogramming [ 153 ] Cardiogenesis Human Samples Provides valuable details about the process of cardiac development [ 154 ] Cardiac Progenitors Histopathology Addresses the development of cardiomyocytes from cardiac progenitors [ 155 ] Heart Field Human Samples Provides valuable details about early stages of cardiac development [ 156 ] Heart Field Histopathology Provides valuable details about early stages of cardiac development [ 58 ] Heart Field ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 14 ] Cardiac Tumors Clinical Details Addresses the topic of cardiac tumors, which is relevant for understanding the etiology and characteristics of cardiac myxoma (CM) [ 15 ] Cardiac Tumors Clinical Details Explores cardiac tumorigenesis [ 20 ] Heart Regeneration Human Samples Provides insights into heart regeneration, a relevant concept for studying the limited regenerative potential of cardiomyocytes. [ 21 ] Cardiac Regeneration Human Samples Explores cardiac regenerative potential [ 22 ] Cardiac Regenerative Pathways Human Samples Essential to investigate the nature of cardiomyocytes [ 23 ] Cardiac Organoids Human Samples Provides step by step progression of the cardiac development [ 24 ] Cardiac Organoids Human Samples Provides insights into the cardiac developmental processes [ 152 ] Cardiac Reprogramming Factors Histopathology Addresses the genetic architecture involved in cardiac reprogramming [ 153 ] Cardiogenesis Human Samples Provides valuable details about the process of cardiac development [ 154 ] Cardiac Progenitors Histopathology Addresses the development of cardiomyocytes from cardiac progenitors [ 155 ] Heart Field Human Samples Provides valuable details about early stages of cardiac development [ 156 ] Heart Field Histopathology Provides valuable details about early stages of cardiac development [ 58 ] Heart Field ...…”
Section: Resultsmentioning
confidence: 99%
“…In this section, this study investigates cardiac myxoma through the lens of developmental biology [ 152 , 153 ]. The CPCs are multi-lineage cells with major expression of Nkx2–5 and Isl1 [ 154 , 155 ].…”
Section: Key Cardiac Transcription Factors/genesmentioning
confidence: 99%
“…The LEFTY-PITX2 signaling pathway plays crucial roles in the maturation of cardiac organoids derived from hiPSC-cardiac mesoderm [123,124]. Using a specific cocktail of growth factors, Sasha Mendjan and coworkers were able to generate self-organizing cardioids using seeding hESCs and hiPSCs in 96-well plates (3D culture) followed by cardiac differentiation; the authors demonstrated that cavity morphogenesis is controlled by the mesodermal Wnt-BMP signaling axis [107], proving that cardioids represent a suitable platform to study mechanisms of cardiogenesis and heart diseases.…”
Section: Cardiac Organoidsmentioning
confidence: 99%
“…Several authors have also reported that a large diversity of epigenetic processes, including the expression of non-coding RNAs (especially microRNAs), histones modifications and DNA methylation, are capable of regulating gene expression, by influencing transcription or inhibiting translation through several functional overlapping and cross-talking mechanisms [23,24]. In particular, microRNAs are considered as a post-transcriptional type of epigenetic regulatory processes, since the degree of complementarity microRNA/target mRNA determines its final outcome, either by degradation or translational inhibition [24,25]. Specifically, miR-1 has been the first essential microRNA identified in cardiac development, with a specific expression pattern in cardiac muscle [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%